2021
DOI: 10.1016/j.celrep.2020.108609
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stiffness Controls Dendritic Cell Metabolism and Function

Abstract: Highlights d Environmental stiffness promotes DC inflammatory function d Tension primes DC metabolism, even without pattern recognition receptor input d TAZ bridges mechanosensory signals to DC metabolism and function d Tension directs phenotypes of human monocyte-derived DCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
125
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 77 publications
10
125
0
1
Order By: Relevance
“…In addition, we uncovered the first detailed molecular mechanism through which keratinocytes integrate chemical and mechanical inputs from the environment to regulate IL-6 production. These findings emphasize biophysical cues, particularly matrix stiffness, as a central regulator of cell signaling in keratinocytes, consistent with previous observations in other cell types (43)(44)(45), and highlight the role of the stiffnessmediated mechanotransduction pathway in enhancing proinflammatory cytokine production in response to external stimuli, such as DNCB (Figure 4G).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we uncovered the first detailed molecular mechanism through which keratinocytes integrate chemical and mechanical inputs from the environment to regulate IL-6 production. These findings emphasize biophysical cues, particularly matrix stiffness, as a central regulator of cell signaling in keratinocytes, consistent with previous observations in other cell types (43)(44)(45), and highlight the role of the stiffnessmediated mechanotransduction pathway in enhancing proinflammatory cytokine production in response to external stimuli, such as DNCB (Figure 4G).…”
Section: Discussionsupporting
confidence: 91%
“…These examples emphasize the need for caution when extrapolating data from one model to the next. Aging immunology studies should also better integrate emerging insights from geroscience, especially from inflammaging research, which has recently described pivotal roles for mitochondrial dysfunction, proteostasis, nutrient sensing and physical changes in the tissue microenvironment in modulating immune pathways [197][198][199][200] .…”
Section: Discussionmentioning
confidence: 99%
“…Physical cues and external stimuli in the microenvironment drive a cell’s physiological function and lead to numerous downstream signaling effects. Piezo1 has been identified as a critical sensor of mechanical stress in numerous myeloid and lymphoid cells, indicating its role in the immune system by linking mechanical forces with immune regulation [ 135 , 136 , 137 , 138 ]. In one study, Piezo1 was determined as the primary sensor of physical forces in myeloid cells, as Piezo1-deficient leukocytes were unable to transduce mechanical signals [ 135 ].…”
Section: Piezo1 In Immune Cellsmentioning
confidence: 99%
“…However, the authors also reported exacerbated autoinflammation in a model of pulmonary fibrosis through the activation of Piezo1 [ 139 ]. Finally, Piezo1 has been shown to play an important role in dendritic cell (DC) activation and function when exposed to mechanical stress [ 138 ]. In this study, Yoda1 strongly upregulated the production of pro-inflammatory cytokines IL-6 and TNF- α [ 138 ].…”
Section: Piezo1 In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation